Preliminary Outcomes of Hypochlorous Acid as an Adjunct for Pocket Irrigation in Revision Aesthetic Breast Surgery. (11th July 2020) - Hasan, Samir; Mujadzic, Mirza; Kaswan, Sumesh; Halpern, Joshua; Van Natta, Bruce; Lund, Herluf
Abstract: Background: Capsular contracture is a challenging problem for plastic surgeons despite advances in surgical technique. Breast pocket irrigation decreases bacterial bioburden. Studies have shown that hypochlorous acid (HOCl; PhaseOne Health, Nashville, TN) effectively penetrates and disrupts biofilms; however, there are limited clinical data regarding this irrigation in breast augmentation. Objectives: The aim of this study was to investigate the effects of HOCl pocket irrigation in revision breast augmentation by evaluating rates of capsular contracture recurrence, infection, and allergic reactions. Methods: We performed an institutional review board–approved retrospective chart review of revision breast augmentation cases for Baker grade III/IV capsular contractures in which pockets were irrigated with HOCl. Data were obtained from 3 board-certified plastic surgeons. Results: The study included 135 breasts in 71 patients, who ranged in age from 27 to 77 years (mean, 53.7 years). Follow-up ranged from 12 to 41 months (mean, 20.2 months). Postoperatively, there were 2 unilateral Baker grade III/IV recurrences at 13 months and 1 bilateral Baker grade II recurrence at 3 months. There were no infections or allergic reactions. The overall Baker grade III/IV capsular contracture recurrence rate was 0% at 12 months and 1.5% at 15 months. Conclusions: Breast pocket irrigation decreases bioburden, which may influence capsular contracture recurrence. We evaluated 3 varied applications of HOCl in revision aesthetic breast surgery and found a low capsular contracture recurrence rate and no adverse reactions. We plan to report our findings with HOCl in primary breast augmentation in the future, and other studies are being conducted on the efficacy of HOCl in aesthetic surgery. Level of Evidence: 4: